Impacto da adoção das IFRS (International Financial Reporting Standards) em indicadores econômico-financeiros: um estudo da caso múltiplo em empresas do setor de transporte aéreo listadas na Bolsa de Valores de São Paulo - Valério, Luiz Henrique (2011)
The increasing adoption of the international financial reporting standards (IFRS) is the result of changes occurred in the last two decades, economy globalization, and the development of international markets. Due to the increased demand for information that allows foreign investors to compare the results of its investments in several companies of different countries with different standards, the adoption of a single accounting standard, globally accepted, became necessary. The International Accounting Standard Board (IASB) was responsible for the preparation of international standards whose process of convergence is already occurring in over 100 countries worldwide. Brazil, with the enactment of Law 11638/07, effective beginning as of January 1, 2008, and subsequent amendments introduced by Law 11941/09, took an important step in the convergence of its standards with international standards through the creation of the Accounting Pronouncements Committee (CPC), agency responsible for the issuance of accounting pronouncements in accordance with IFRS. IFRS 1, denominated First-Time Adoption, refers to the requirements for the first year the company discloses its financial statements pursuant to local accounting standards and IFRS. Accordingly, the purpose of this study is to verify whether in the air transportation industry, the first-time adoption of IFRS 1 resulted in significant changes in the main financial indicators and which are the impacts of IFRS adoption to the organization as a whole. For this, a research methodology that contemplates the study of an exploratory multiple case with a direct study of the companies information was chosen to characterize it and obtain the required data for the research. The comparative analysis of the financial statements of the companies that are the object of this study and the results obtained from the questionnaire and interviews indicated that financial statements prepared in accordance with IFRS present a higher disclosure level than those financial statements prepared in accordance with BRGAAP. We concluded that the adoption of IFRS impacts not only financial indicators, but several processes and controls of the companies as a whole